Succinate dehydrogenase governs the sensitivity to SDHI fungicides and fruit pathogenicity of Colletotrichum gloeosporioides - He Zhang; Zi Ye; Shiyou Yang; Mengting Zhang; Yang Xia; Zhixin Liu; Yu Sun; Jian Li; Xi Li; Zhengjie Zhu; Jinji Pu (Journal of Agriculture and Food Research)
Succinate dehydrogenase inhibitor (SDHI) fungicides are widely used to control plant anthracnose caused by Colletotrichum gloeosporioides. However, C. gloeosporioides resistant to SDHI fungicides have emerged in the orchard, also carry significant environmental risks. The thifluzamide, boscalid, and fluopyram are commonly used SDHIs fungicides in plant protection. In the study, the inhibitory activity of thifluzamide, boscalid, fluopyram against 55 C. gloeosporioides strains from China were determined, including mycelial growth and conidial production. The three SDHIs fungicides could inhibit the growth of mycelia and production of conidia of C. gloeosporioides. Here, we identified SDH subunits of C. gloeosporioides and expression patterns, and obtained CgSDHB, CgSDHC, CgSDHD mutants of C. gloeosporioides using CRISPR/Cas9 gene editing system. Biochemical evidence suggests that the mutants have reduced tricarboxylic acid cycle efficiency, thereby increasing the susceptibility of SDHIs and decreasing pathogenicity to multiple hosts. These results improve our understanding of SDHIs antifungal mechanism in C. gloeosporioides and provide new insights into the pathogenesis of SDH subunits regulation.